PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE MEREK OPPO DI PONOROGO - Juliawati Juliawati; Adi Santoso; Sri Hartono (Bajang Institute, 2023)
The purpose of this study was to determine the effect of product quality, price and promotion on purchasing decisions for OPPO brand smartphone products in Ponorogo. The population of this study were students of the Management Study Program, Faculty of Economics, Muhamamdiyah University, Ponorogo. the number of samples of this study were 53 samples. The sampling method uses the random sampling method, namely determining the sample chosen randomly because all populations have the same opportunity to be used as a sample. The data collection method in this study used a research questionnaire. The method of analysis uses multiple linear regression analysis with instrument tests namely validity and reliability tests, as well as hypothesis testing. The results of this study found that product quality, price and promotion partially had a significant influence on product purchasing decisions, OPPO smartphones among students of the Management Study Program, Faculty of Economics, University of Muhamamdiyah Ponorogo